PENGARUH REBUSAN KAYU MANIS TERHADAP NYERI JAHITAN PERINEUM PADA IBU NIFAS DIPMB KHUSNIA,S.ST.bd DESA TAMBAK LEKOK KEC. LEKOK KAB.PASURUAN - Salsabila, Salsabila; Purwanti, Anik Sri; Widiatril, Raden Maria Veronika (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The postpartum period is the period during labor and immediately after birth which includes the following weeks when the reproductive tract returns to its normal non-pregnant state (Noviana Evin, 2018). Pain is a form of discomfort, which is defined in various perspectives. Stitching pain is pain that occurs in the perineum due to the suturing/hectating process due to tearing of the birth canal during the birth process, whether torn spontaneously or due to an episiotomy (scientific, 2017). Birth canal tears occur when the perineal tissue is torn during childbirth. According to (Zuliati 2016) 65% of birth canal tears occur in mothers in the second stage when giving birth to a baby. This wound usually occurs spontaneously or occurs due to an episiotomy. To determine whether there is an effect of cinnamon decoction on perineal suture pain in PMB Khusnia in Tambak Lekok Village, Kec. Lekok, Pasuruan Regency. The type of research used was a purposive sampling technique, the method used was quantitative with pre-experiment one group pretest-posttest design. The population in this study was postpartum mothers on days 1-6 based on data available in Khort in January-March 2024, obtained by mothers postpartum with perineal suture pain as many as 20 people 20% of the total 28% analysis used Wilcoxon signed rank test. The results of the Wilcoxon signed rank test showed that the effect of giving cinnamon decoction on perineal suture pain in postpartum mothers, the results were 0.005 where <0.05, which means there was an effect before and after being given cinnamon decoction. Giving cinnamon decoction can reduce the pain of perineal stitches in postpartum mothers.